A Study on Mobile Based Agro-advisory in Meghalaya (Indian Journal of Extension Education, 2019)
The ICT is a partial tool to enhance the productivity and profitability of the farmer. Various initiatives in IT (Information Technology) were launched in the state to boost up the yield of crops in order to enhance the livelihood and income of the farmers. Among the initiatives one agro-advisory laboratory has been established under the programme of “Development and Deployment of Mobile based Agro- advisory system in North-East India (hereafter m4agriNEI)” in College of Post Graduate Studies, Central Agricultural University, Barapani. The present study was conducted in 11 villages of Ri-Bhoi district of Meghalaya. Over 218 farmers were randomly selected from the eleven villages. Data were collected by using pre-tested structured interview schedule through personal interview method. The tabular analysis was done to study the perception and accrual of benefits of the programme for the farmers located in remote villages. The farmers expressed that the information gathered through agro-advisory were very useful and helpful for them. The programme has gained lot popularity among the farmers of Meghalaya and the sufficient numbers of beneficiaries were found to be benefitted by using the agro-advisory in the crop as well as in livestock sector. Among the crops, the ginger crop being a cash crop of the state need more care right from its planting to harvesting. The agro-advisory on complete package and practices especially in selection of rhizome, its treatment, maintaining spacing during the planting and also the tips of proper care during harvesting provided by experts of agro-advisory really became the boon in production of ginger in the state. Providing the artificial insemination and vaccination in pig and piglets encouraged the farmers to come forward to access more and more information from Agro-advisory services. Keeping the success in view the funding agency has extended the finance support two times. Hence, to provide the agro advisory in sustainable manner, the Government of Meghalaya taken over the Laboratory which has added one more component viz, mobile marketing vans for agri-produce from farmers to market in the state